A crackle of crickets : a compilation of insect collective nouns. (PatrickGeorge, 2012)
A plague of locusts, a flock of lice, a colony of ants: these are some of the insect collective nouns you may already know. But have you heard of a loveliness of ladybirds, a clew of worms, or a kaleidoscope of butterflies? Then turn the pages of this book to discover a collection of lesser-known and sometimes more fanciful terms, and hope that you will never be forced to encounter a ghost of knats or a bike of wasps- but if you do at least you'll know what to call them!